The Impacts of Self-Efficacy on EFL Learners’ Speaking Skills - Wijaya, Kristian Florensio (Journal of Education, Language Innovation, and Applied Linguistics, 2024)
In L2 speaking learning contexts, highly self-efficacious EFL learners are characterised as speakers capable of sharing their ideas confidently with other interlocutors as they have put a higher degree of belief towards their current speaking competencies. In support of self-efficacy, EFL learners are strongly willing to proceed with the complex speaking learning processes as they are prompted to foster their L2 communicative competencies to the utmost level. This small-scale library study was initiated to reveal the potential impacts of self-efficacy on EFL learners’ speaking skills. To achieve the primary study objective, 30 previous self-efficacy studies were profoundly reviewed with a thematic analysis to yield more understandable and trustworthy research results. Based on the obtained research results, it is strongly suggested that second language-speaking learning instructors infuse the robust construction of self-efficacy within EFL learners since they can progressively transform into more successful and confident L2 speakers. In conclusion, a higher degree of self-efficacy growth allows EFL learners to persistently confront various speaking learning impediments due to the successful employment of their speaking learning strategies mutually interlinked with the current speaking learning situations.   Keywords: Self-efficacy; Speaking skills; EFL learners.